The Relationship Between Lecturers' Teaching Styles and Learning Motivation of Students in the Primary School Teacher Education Program - Inayah, Inayah; Mardhotillah, Putri; Falahiyah, Titi; Mutiari, Puspa Intan; Safitri, Lia; Halala, Khairul Nisa; Juhji, Juhji; Paiman, Paiman; Mansur, Mansur (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study analyzes the relationship between lecturers' teaching styles and students' learning motivation in higher education. Teaching style is an external factor significantly influencing student engagement and academic achievement. The study used a quantitative approach with a correlational method. The study sample consisted of 120 Elementary Madrasah Teacher Education Study Program students at Sultan Maulana Hasanuddin State Islamic University, Banten, selected through proportional stratified random sampling. The instruments used included the Teaching Style Inventory and the Academic Motivation Scale, which had been tested for content validity and reliability. Data were analyzed using descriptive statistics and the Pearson product-moment correlation test. The results showed a strong positive relationship between lecturers' teaching styles and students' learning motivation (r = 0.672; p 0.001). The Facilitator dimension had the highest correlation (r = 0.701), followed by Personal Model and Expert. This finding is consistent with Self-Determination Theory, which emphasizes the importance of fulfilling the needs for autonomy, competence, and relatedness to increase students' intrinsic motivation. These findings recommend that lecturers optimize facilitative approaches, serve as academic role models, and provide constructive feedback. Universities are advised to facilitate ongoing pedagogical training to improve the quality of teaching styles oriented toward student empowerment.